Preconceito e estereótipos relativos a cor, sexo e status - Moreira, Angela Maria Venturini (1988)
This study is an investigation of positive and negative stereotypes, as a function of colour, sex and status. The instrument used consisted of eight stimulus drawings, four men and four women, in this way: white rich man, black rich man, white poor man, black poor man, white rich woman, black rich woman, white poor woman and black poor woman, which had been distributed in equity among the sample subjects; in a questionnaire with nine objective itens, elaborated to measure the stimulus' social distance, instruction, work hierarchy position, job and the ones about the parents, to investigate the social mobility and socio-economic status, and one opened item to catch the sample's perception about the stimulus-drawing. The sample was composed of 930 subjects: 482 subjects of white skin and white physical signs (mouth, hair and nose) and 448 subjects of black skin and black physical signs, or white skin and black physical signs, or black skin and white physical signs, so labeled by the experimenter. This sample classified themselves as 602 'white' subjects and 328 black subjects. The basic ·hypothesis tested was the following: 'There are positive and negative stereotypes related to colour, sex and status.' The only item, in which the basic null hypothesis was rejected, was the one about the job of stimulus drawings, where white samples, labeled by the experimenter and by themselves, and black sample labeled by themselves as white, rejected it in the variables sex and status, suggesting that stereotypes appears according to ocupations given to drawings' sex and status. The black ones, labeled by the experimenter and by themselves, rejected it in the three variables, showing that colour, sex and status, disconnectly, influenced upon stereotypes through the ocupation given to stimulus, beside the interaction colour x status, suggesting the ocupational stereotype too, when the colour is associated to drawings' status. The black sample, labeled by the experimenter, also rejected it in the interation colour x sex x status, suggesting discrimination over the ocupations given to stimulus, when those three variables are associated. The white samples, labeled by the experimenter and by themselves, showed ambiguous answers in the great part of the itens. The black ones, labeled by the experimenter and by themselves, exhibited answers without significant differences in some itens. The ABIPEME socio-economic status scale displayed both samples white and black, labeled by the experimenter, presented high level of instruction and good socio-economic status. There were more women than men, in both samples, though men and women were equivalent in both white and black samples, suggesting that white and black women and black men behaved themselves according to cultural and dominant values, demonstrating low self-depreciation and low self-esteem.